NIME Principles & Code of Practice on Ethical Research - Morreale, Fabio; Gold, Nicolas; Chevalier, Cécile; Masu, Raul; Ergener, Kerem; Cavdir, Doga; Fuchs, Natalia (Zenodo (CERN European Organization for Nuclear Research), 2025)
NIME upholds the highest ethical standards in research and artistic practice by recognising the importance of individual persons and data as an expression of personhood. These standards also include ethical values that are not always a concern of institutional research committees, including inclusivity, accessibility, animal rights, socio-economic fairness, and environmental awareness. The complete NIME Principles & Code of Practice on Ethical Research can be found at: www.nime.org/ethics.
Keywords: Artistic and Creative Research; Animal testing and alternatives; Art, Politics, and Modernism